Sublittoral and bathyal sea cucumbers (Echinodermata: Holothuroidea) from the Northern Mozambique Channel with description of six new species - Samyn, Yves; Vandenspiegel, Didier (Zootaxa, 2016)
The 2009 expedition with the research vessel Miriky sampled the sublittoral and bathyal waters of the northern Mozambique Channel. This exploration campaign resulted in a small, but very diverse collection of holothuroids comprising 174 specimens representing 31 species, 18 genera, 10 families and 5 orders. Of these species, many were hitherto unknown for Madagascar or even for the Indian Ocean, and six, Bathyplotes aymeric sp. nov., Holothuria (Cystipus) yann sp. nov., Holothuria (Stauropora) bo sp. nov., Holothuria (Metriatyla) alex sp. nov., Holothuria (Theelothuria) cyrielle sp.nov., Molpadia thandari sp. nov., are new to science. Molpadia lenticulum (Cherbonnier & Féral, 1981) is a new combination. This contribution provides an illustrated and annotated overview of the poorly known, highly biodiverse, sublittoral and bathyal sea cucumber fauna of the northern Mozambique Channel. Our findings demonstrate how ignorant we are about the poorly explored habitats of our planet and therefore stress the urgent need for more explorations to such regions.